The effects of mental fatigue on long-term endurance performance - Gattoni, C.; O'Neil, B. V.; Marcora, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Mental fatigue is a psychobiological state caused by prolonged and demanding cognitive activity (Boksem et al. 2008). It has been previously demonstrated that mental fatigue has negative effects on perception of effort and endurance performance during laboratory tests lasting between 4 and 25 minutes (Marcora et al. 2009; Pageaux et al. 2013; Brownsberger et al. 2013). However, the effects of mental fatigue on longer term endurance performance and on the field have never been tested. Therefore, the main aim of the current study was to investigate the effects of mental fatigue on perception of effort, heart rate, pacing and performance during a simulated half-marathon race in amateur runners. METHODS: Sixteen amateur marathon runners (means ± SD: age 41.9 ± 9.1 yr, body mass 75.1 ± 7.8 kg, height 1.76 ± 0.06 m) were randomly allocated to either a group performing a 50-min mentally-fatiguing task before the half-marathon, or a control group (reading magazines for 50 min before the half-marathon). All subjects completed psychological questionnaires and fatigue visual analogue scales before and after experimental treatment, and after the half-marathon. Performance time, speed, heart rate and rating of perceived exertion (RPE) were measured during the simulated race. RESULTS Runners who performed the mentally-fatiguing task completed the half-marathon approximately five minutes slower (6,664 ± 860 s) than the control group (6,358 ± 634 s) (Cohen`s d = 0.41; p = 0.432). Practically, the true effect size at the population level is possibly harmful (65.6% probability), unlikely trivial (22.1% probability) and unlikely beneficial (12.3% probability). DISCUSSION: In conclusion, because of low statistical power, the data collected so far do not provide reliable evidence that mental fatigue reduces long-term endurance performance. However, magnitudebased inference suggests that mental fatigue is possibly harmful to half-marathon performance in amateur runners. Additional data will be collected to draw a firmer conclusion on the null hypothesis and provide more precise estimates of the effects of mental fatigue on long-term endurance performance.